Does Uranium Mining Increase Civil Conflict Risk? Evidence from a Spatiotemporal Analysis of Africa from 1945 to 2010 - Carlo Koos; Matthias Basedau (German Institute of Global and Area Studies (GIGA), 2012)
We employ a two-tier spatiotemporal analysis to investigate whether uranium operations cause armed conflict in Africa. The macrolevel analysis suggests that - compared to the baseline conflict risk - uranium ventures increase the risk of intrastate conflict by 10 percent. However, we find ethnic exclusion to be a much better predictor of armed conflict than uranium. The microlevel analysis reveals that uranium-spurred conflicts are spatiotemporally feasible in four countries: the Democratic Republic of Congo (DRC), Namibia, Niger and South Africa. We find strong evidence in the case of Niger, and partial evidence in the case of the DRC. Namibia and South Africa do not yield substantial evidence of uranium-induced conflicts. We conclude that uranium may theoretically be a conflictinducing resource, but to the present day empirical evidence has been sparse as most countries are still in the exploration phase. Considering that the coming years will see 25 African countries transition from uranium explorers into producers, we strongly suggest that our analysis be revisited in the coming years.
Keywords: 300; civil war; uranium; ethnicity; GIS; subnational study